A Challenge to Adjustment: Types of Personality Influenced Loneliness and Learning Styles in the University Life of New Students - Saili, Jamayah; Madihie, Amalia; Abu Bakar, Rizal (2005)
Adjustment or coping is a behavior that permits us to meet the demands of the environment (Rathus & Nevid, 1992). After completed the study in secondary school, the students now pursue their studies where they need to make some psychological demanding adjustments such as leaving home for the first time, a job interview, and new friends and environment. These demanding adjustments can contribute to the stress to the new students who enrolled to the university for the first time. According to Rathus and Nevid, as an active human being, we must accommodate and extend the concept of adjustment includes self-initiated growth and development along intellectual, emotional, social, physical, and vocational dimensions. This study was to investigate how personality of the new student influences the students’ learning styles and loneliness aspects when enrolled to the university for the first time and how they adjusted or coped with their new environment. A set of questionnaire is given to the new students in the early of the first semester that combined three components: personality, learning styles, and loneliness scales. In this study, correlation between the demography (such as gender, age, background, and education level), learning styles and personality with the loneliness levels will be run and discussed. The implication of adjustment in the new university life and the importance of understanding the impact of the psychological aspects' will be discussed at the end of the study.